Esterifikasi Gliserol Dari Produk Samping Biodiesel Menjadi Triasetin Menggunakan Katalis Zeolit Alam - Nirmala Sari; Zuchra Helwani; Hari Rionaldo (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2015)
Glycerol is a by-product of biodiesel production from transesterification reaction generated 10% volume product. The increase of biodiesel production is followed by the increase of the glycerol as by product. Glycerol when esterified with acetic acid formed Triacetin. Triacetin has many uses for food, non-food and additives in biofuel feedstock that is renewable and environmentally friendly. In this study will be make Triacetin from reaction esterification of crude glycerol purified with acetic acid glacial and using natural zeolite catalyst has been activated. Making triacetin performed with a three-neck flask equipped with a condenser, heating mantle, thermometer and magnetic stirred at 100 ° C, 100 mesh size catalyst and reaction time for 4 hours. Process of qualitative analysis using FT-IR instrument has detected the exixtence of Triacetin product. The variables are varied ratio reactant of glycerol and acetic acid, and the concentration catalyst. The highest conversion obtained for 90.02% in reactan ratio mol glycerol and acetic acid 1: 7, catalyst concentration of 3% to weight of acetic acid. Comparison of reagents give real effect to the conversion of glycerol into Triacetin, while the catalyst concentration does not give a significant effect on glycerol conversion be Triacetin.Keywords: acetic acid, esterification, glycerol, Triacetin